Byyhakh ‘knife’ in the Yakut Linguistic Worldview - Skryabina, Alevtina A. (The New Research of Tuva, 2026)
The article presents a linguoculturological analysis of the concept “byyhakh” ‘knife’ in the Yakut (Sakha) linguistic worldview, drawing on a corpus of lexicographic, paremiological, and folklore sources. The study examines the conceptual core of the term, represented by the lexeme “byyhakh” and its ramified synonymy and specific differentiation (badaaiy, batas, batyya, ürüöh, khotokhoon, gend’yee, ürüöh). Attention is paid to the image of the knife in traditional culture and its symbolic association with masculinity; the article considers its functions as an anthropometric standard and as a semiotic indicator of kinship relations, as reflected in proverbs and folklore.The analysis reveals profound sacralization of the artifact. A range of euphemistic substitutes (kyryylaakh, otoyor, and others) used in hunting practice is identified and described, indicating the inclusion of the knife in a sphere of ritualized communication and taboo. It is established that the concept performed key functions in ritual practices: it acted as an instrument of shamanic mediation, a powerful protective charm, and an object governed by strict behavioral norms.The article concludes that the status of the Yakut knife has undergone transformation in modern times: from a utilitarian-ritual object it has become one of the key representative brands and material symbols of the ethnocultural identity of Yakutia. The study confirms that the concept “byyhakh” ‘knife’ constitutes a multidimensional formation in which linguistic, mythological, social, and axiological codes of the Sakha people are intertwined.
Keywords: cultural concept; byyhakh; knife; Yakut language; Yakuts; Yakut culture; linguistic worldview; euphemization; linguistic taboo